Meta-analysis of the Age-Dependent Efficacy of Multiple Sclerosis Treatments - Weideman, Ann Marie; Tapia-Maltos, Marco Aurelio; Johnson, Kory; Greenwood, Mark; Bielekova, Bibiana (Frontiers in Neurology, 2017)
Objective: To perform a meta-analysis of randomized, blinded, multiple sclerosis (MS) clinical trials to test the hypothesis that efficacy of immunomodulatory disease-modifying therapies (DMTs) on MS disability progression is strongly dependent on age. Methods: We performed a literature search with pre-defined criteria and extracted relevant features from 38 clinical trials that assessed efficacy of DMTs on disability progression. We fit a linear regression, weighted for trial sample size and duration, to examine the hypothesis that age has a defining effect on the therapeutic efficacy of immunomodulatory DMTs. Results: More than 28,000 MS subjects participating in trials of 13 categories of immunomodulatory drugs are included in the meta-analysis. The efficacy of immunomodulatory DMTs on MS disability strongly decreased with advancing age (R2 = 0.6757, p = 6.39e-09). Inclusion of baseline EDSS did not significantly improve the model. The regression predicts zero efficacy beyond approximately age 53 years. The comparative efficacy rank derived from the regression residuals differentiates high and low efficacy drugs. High efficacy drugs outperform low efficacy drugs in inhibiting MS disability only for patients younger than 40.5 years. Conclusions: The meta-analysis supports the notion that progressive MS is simply a later stage of the MS disease process and that age is an essential modifier of a drug efficacy. Higher efficacy treatments exert their benefit over lower efficacy treatments only during early stages of MS, and, after age 53, the model suggests that there is no predicted benefit to receiving immunomodulatory DMTs for the average MS patient.